Extended Neoadjuvant Chemotherapy in Delayed Primary Resection of Ewing Sarcoma During the COVID-19 Era: A Case Report. Issue 2 (13th April 2023) - Arunwatthanangkul, Patcharapol; Rangchaikul, Nutnicha; Anuwongworavet, Supitcha; Chobpenthai, Thanapon
Abstract : Case: A 13-year-old adolescent boy visited our hospital with a growing mass on his left leg. Investigations and examinations were performed to obtain a final diagnosis of Ewing sarcoma in the head of the left fibula with lung metastasis. Neoadjuvant chemotherapy was extended to 11 courses with radiation before wide tumor resection could be performed. The final 3 adjuvant chemotherapy courses were administered to complete the original protocol while surgical resection complications were also treated. The pathological report revealed free margin resection with nonviable tumor cells. Conclusion: An extended neoadjuvant chemotherapy regimen with additional radiation therapy for Ewing sarcoma provided extra local control and allowed limb salvage.